PRACTICALITY OF USING BROWN’S RUBRIC AS A TOOL IN ASSESSING STUDENT’S WRITING SKILL - Nur Hidayah; Veni Roza; Leli Lismay (Journal of English Language and Education, 2021)
This research was due to some problems found in the field. It has been done at SMA KEC X KOTO because most of the teachers of Senior High School still used traditional technique in evaluating students’ writing. The teacher assessed only the accuracy in the use of tense and word spelling, teacher crossed out of words that are considered wrong without giving an explanation and teacher gave assessments to students’ writing without clear criteria, so that the assessment was done subjective. This research used descriptive quantitative research. The researcher used a questionnaires and documentation collect the data. The population of this research was SMA KEC X KOTO. The samples that English teacher at SMA N 1 X KOTO, SMA AL HIRA, SMA NURUL IKHLAS consist 10 teachers by using total sampling. The data were got through questionnaires consists 29 list question items that teachers must answer based on their opinion. To analyze the data, researcher used Likert Scale and then, to find out percentage of each item of questionnaire, the researcher used the formula by Sudijono p:f /n x 100% , after that researcher interpreted of the practicality percentage table. The finding reveals that Brown’s rubric using students writing at SMA X KOTO is very practical. Mostly teacher respond to every statements such as the organization which consists of 8 indicators only answer strongly agree and agree. The interpretation table shows that the percentage of teacher’s mean score was 89%. Thus, the use Brown’s rubric as a tool in assessing students writing was very practical ( 86% - 100%). It is recomended for teachers to use Brown’s Rubric. Key word: Writing, Analytic rubric, Very Practical